Novel Etiological and Therapeutic Strategies for Neurodiseases: Mechanisms and Consequences of Febrile Seizures: Lessons From Animal Models - Ryuta Koyama; Norio Matsuki (Elsevier, 2010)
Febrile seizures (FS) are the most common type of convulsive events in infancy and childhood. Genetic and environmental elements have been suggested to contribute to FS. FS can be divided into simple and complex types, the former being benign, whereas it is controversial whether complex FS have an association with the development of temporal lobe epilepsy (TLE) in later life. In the hippocampus of TLE patients, several structural and functional alterations take place that render the region an epileptic foci. Thus, it is important to clarify the cellular and molecular changes in the hippocampus after FS and to determine whether they are epileptogenic. To achieve this goal, human studies are too limited because the sample tissues are only available from adult patients in the advanced and drug-resistant stages of the disease, masking the underlying etiology. These facts have inspired researchers to take advantage of well-established animal models of FS to answer the following questions: 1) How does hyperthermia induce FS? 2) Do FS induce neuroanatomical changes? 3) Do FS induce neurophysiological changes? 4) Do FS affect the behavior in later life? Here we introduce and discuss accumulating reports to answer these questions. Keywords:: childhood seizure, epilepsy, hippocampus, dentate gyrus, granule cell, neurodisease